Pengembangan Instrumen Penilaian Psikomotor Berbasis IT dalam Pembelajaran Penjasorkes Materi Lompat Jauh pada Siswa SMP - Patria, Lalu Demung; Djuniadi, Djuniadi (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2015)
The purpose of this study is to produce an IT-based psychomotor assessment instrument in learning the penjasorkes on the long jump material in junior high school students. This research uses research and development (R & D) method by adopting Rowntree development model. The stages in the development of assessment instrument consists of three stages: 1) phase I is the planning stage, 2) phase II that is development stage, 3) stage III that is evaluation stage. Data collection techniques in this development using expert validation test and questionnaire practicality psychomotor assessment instrument. Validation value of validator equal to 84,37% and practical value from observer equal to 82,28%. Based on the acquisition of these values, the developed psychomotor assessment instruments fall into the category of valid and practical